1999
DOI: 10.1002/(sici)1097-0142(19990901)86:5<782::aid-cncr13>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a new classification system for curatively resected colorectal adenocarcinoma

Abstract: BACKGROUND The parameters within which colorectal adenocarcinoma is currently staged are often insufficient for decisions regarding therapy after potentially curative surgery. Consequently, oncologists make frequent use of additional prognostic indicators when assessing individual prognosis and selecting patients for adjuvant systemic treatment. Follow‐up programs are generally uniform for all patients, regardless of disease stage and prognosis. As a result, patients with a favorable prognosis are needlessly s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 70 publications
0
8
0
2
Order By: Relevance
“…23 Dirschmid et al, 20 Horn et al, 16 17 and Blumberg and colleagues 24 recommend considering venous invasion as an indicator for the administration of systemic adjuvant treatment. Based on our study of 231 consecutive curatively resected patients with CRC, 22 in which we found that distant metastases developed in 50% of the venous invasion positive patients, and in only 36% of the node-positive patients, we are inclined to agree with these authors.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…23 Dirschmid et al, 20 Horn et al, 16 17 and Blumberg and colleagues 24 recommend considering venous invasion as an indicator for the administration of systemic adjuvant treatment. Based on our study of 231 consecutive curatively resected patients with CRC, 22 in which we found that distant metastases developed in 50% of the venous invasion positive patients, and in only 36% of the node-positive patients, we are inclined to agree with these authors.…”
Section: Discussionmentioning
confidence: 78%
“…Venous invasion may be used to enhance the power of existing staging systems as predictors of individual prognosis by subdividing stages according to the presence or absence of venous invasion, 21 or it may be combined with other variables to form a completely new classification of CRC. 22 According to the National Institutes of Health consensus statement on adjuvant treatment of CRC, regional lymph node status is currently the main indicator for the administration of systemic adjuvant treatment. 23 Dirschmid et al, 20 Horn et al, 16 17 and Blumberg and colleagues 24 recommend considering venous invasion as an indicator for the administration of systemic adjuvant treatment.…”
Section: Discussionmentioning
confidence: 99%
“…8 As far as vascular invasion is concerned, it is still unclear whether different types of vascular invasion (lymphatic or venous) are prognostically relevant as independent factors. 9 A proposal to include venous invasion among stage influencing factors in colorectal cancer has already been made [10][11][12] and it is still being debated as to whether this finding per se may have clinical implications on tumor staging. 13 In this regard, we believe that grouping tumor deposits with other types of vascular invasion will account for the prognostic heterogeneity of these particular lesions.…”
mentioning
confidence: 99%
“…La recidiva dopo l'intervento chirurgico spesso rappresenta una rilevante causa di morte. La prognosi è correlata al grado di coinvolgimento della parete viscerale e all'interessamento dei linfonodi [34], altri fattori prognostici rilevanti sono il grading, l'invasione vascolare [35], l'invasione perineurale, il numero dei linfonodi interessati. I più recenti fattori prognostici sono le mutazioni genetiche p53, KRAS, EGFR, l'indice di proliferazione.…”
Section: Prognosiunclassified
“…I più recenti fattori prognostici sono le mutazioni genetiche p53, KRAS, EGFR, l'indice di proliferazione. L'occlusione e la perforazione intestinale sono indici prognostici negativi [35], così come livelli sierici pre-trattamento dell'antigene carcino-embrionario (CEA) e dell'antigene carboidratico 19-9 (CA 19-9) [36]. Tra i fattori correlati al paziente, il perfomance status (ovvero le condizioni generali) in- fluenzano in maniera importante il risultato del trattamento terapeutico [37], con tassi di risposta ai comuni regimi chemioterapici del 30-60% nei pazienti con perfomance status di 0, del 10-30% e 0-10% nei casi di performance status di 1 e 2, rispettivamente.…”
Section: Prognosiunclassified